Design of Rejection Subsystem for Abnormal Workpiece Condition Modular Production System at Distribution Station - Christopher Adryan Ichsan; Agustinus Purna Irawan; Agus Halim; Didi Widya Utama; William Dae Panie; Bright Levin Tolukun (Fakultas Teknik Universitas Pancasila, 2024)
In the industrial era 4.0, the automation system technology used is growing rapidly. Automation systems in the industry are very useful, especially in reducing production time. One of the tools that can be used to simulate production in an industry is the Modular Production System (MPS). MPS itself consists of several stations to simulate the production process on a small scale. In a production system, of course, a system is needed that can detect abnormal workpiece conditions. This system will be driven by a Programmable Logic Controller (PLC). This system will be placed at the distribution station. The rejection system in MPS is needed because, in MPS there is still a manual process, namely in the process of inserting workpieces into the stack magazine. with this manual process, it is likely that workpieces with abnormal conditions will be processed by MPS. This condition is unlikely to be processed further to the pick and place station. Therefore, objects with abnormal conditions must be separated by this rejection system. There are 2 methods used to conduct this research, namely using the 5/3 valve and the positive stop method. Data collection from both methods is done by experiment. From the experimental results of the two methods, it can be seen that the best method used for this system is the positive stop method. This method is the most appropriate method because it can produce a very accurate swivel arm stop position. From the data obtained, using the 5/3 valve method with a pressure of 4 bar the swivel arm stop position ranges from 22.4 cm to reach more than 25.8 cm, and at a pressure of 5 bar the swivel arm height ranges from 25.8 cm to more. By using the positive stop method the swivel arm stops exactly at the specified swivel arm height because the swivel arm is held by the pneumatic cylinder.